A Synthetic Agonist to Vasoactive Intestinal Peptide Receptor-2 Induces Regulatory T Cell Neuroprotective Activities in Models of Parkinson’s Disease - Mosley, R. Lee; Lu, Yaman; Olson, Katherine E.; Machhi, Jatin; Yan, Wenhui; Namminga, Krista L.; Smith, Jenell R.; Shandler, Scott J.; Gendelman, Howard E. (Frontiers in Cellular Neuroscience, 2019)
A paradigm shift has emerged in Parkinson’s disease (PD) highlighting the prominent role of CD4+ Tregs in pathogenesis and treatment. Bench to bedside research, conducted by others and our own laboratories, advanced a neuroprotective role for Tregs making pharmacologic transformation of immediate need. Herein, a vasoactive intestinal peptide receptor-2 (VIPR2) peptide agonist, LBT-3627, was developed as a neuroprotectant for PD-associated dopaminergic neurodegeneration. Employing both 6-hydroxydopamine (6-OHDA) and α-synuclein (α-Syn) overexpression models in rats, the sequential administration of LBT-3627 increased Treg activity without altering cell numbers both in naïve animals and during progressive nigrostriatal degeneration. LBT-3627 administration was linked to reductions of inflammatory microglia, increased survival of dopaminergic neurons, and improved striatal densities. While α-Syn overexpression resulted in reduced Treg activity, LBT-3627 rescued these functional deficits. This occurred in a dose-dependent manner closely mimicking neuroprotection. Taken together, these data provide the basis for the use of VIPR2 agonists as potent therapeutic immune modulating agents to restore Treg activity, attenuate neuroinflammation, and interdict dopaminergic neurodegeneration in PD. The data underscore an important role of immunity in PD pathogenesis.